The prognostic value of preoperative plasma fibrinogen in Asian patients with urothelial cancer: a systematic review and meta-analysis - Bao, Zhengqing; Li, Guizhong; He, Feng; Xu, Xiao; Liu, Zhenhua; Wang, Jianwei (Frontiers in Endocrinology, 2024)
Objective: We conducted this meta-analysis to comprehensively explore the prognostic value of the preoperative plasma fibrinogen in Asian patients diagnosed with urothelial cancer (UC).Methods: After a systematic search of Web of Science, PubMed, and Embase before May 2024, we included 10 studies in our meta-analysis. The hazard ratios (HRs) with 95% confidence interval (CI) for overall survival (OS), cancer-specific survival (CSS), recurrence-free survival (RFS), and progression free survival (PFS) were estimated using fixed effect model.This meta-analysis included a total of 2875 patients. UC patients with an elevated preoperative plasma fibrinogen had worse OS (pooled HR: 2.13, 95% CI: 1.81-2.51; P<0.001), CSS (pooled HR: 2.22, 95% CI: 1.83-2.70; P<0.001), RFS (pooled HR:1.90, 95% CI: 1.59-2.27; P<0.001), and PFS (pooled HR: 2.12, 95% CI: 1.36-3.29, P=0.001). No significant heterogeneity or publication bias was found. Additionally, statistically significant pooled HRs were also calculated in subgroup analysis when stratified by cancer type, country, and cut-off value.The presence of elevated preoperative plasma fibrinogen levels is significantly correlated with unfavorable tumor outcomes in UCs.